1999
DOI: 10.1002/hep.510290229
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Before and After Liver Transplantation for Cholestatic Liver Disease

Abstract: Liver transplantation (LT) is an established therapy for patients with end-stage primary biliary cirrhosis (PBC) or primary sclerosing cholangitis (PSC). In this report, we describe the health status and quality of life (QOL) in patients with these cholestatic liver diseases before and after LT. A QOL questionnaire was completed by 157 adult patients with PBC or PSC before and 1 year after liver transplantation at the Mayo Clinic or Baylor University Medical Center. This questionnaire measured four aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
121
0
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 23 publications
3
121
0
10
Order By: Relevance
“…A substantial number of studies found that HRQL improved markedly after OLT. [1][2][3][4][5][6] HRQL of liver transplant recipients seemed close to that of general populations, but somewhat lower. [7][8][9][10][11] The difference was more evident in physical than mental areas, and most studies found that liver transplant recipients experienced physical limitations and symptoms several years after OLT.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…A substantial number of studies found that HRQL improved markedly after OLT. [1][2][3][4][5][6] HRQL of liver transplant recipients seemed close to that of general populations, but somewhat lower. [7][8][9][10][11] The difference was more evident in physical than mental areas, and most studies found that liver transplant recipients experienced physical limitations and symptoms several years after OLT.…”
mentioning
confidence: 78%
“…[7][8][9][10][11] The difference was more evident in physical than mental areas, and most studies found that liver transplant recipients experienced physical limitations and symptoms several years after OLT. 2,[7][8][9]12,13 Fatigue has been found to be a common problem among liver transplant recipients. 2,[7][8][9]12,13 One follow-up study found that 157 patients with cholestatic liver disease experienced less fatigue after OLT, but fatigue still remained the most frequent symptom 1 year after OLT.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…14 The instrument version used in this study was previously validated for LT and non-LT patients. 17,18 It consists of 87 items and addresses the following domains: liver disease symptoms, Karnofsky performance status, 19 health perception, and index of well-being.…”
Section: Qol Instrumentmentioning
confidence: 99%